(3eHOC GdSjGOI GdhWfjI hfXGe GdMeGjI GdOhdjI dMbhb GdGfSGf (B/ s - (3eMeO YhV GdZeQis; (3UdGM GdOjf YGeQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3Gf efWdb gPg GdOQGSI hLhgQgG cGf HMK ehVhY GdYdGbI Hjf eHOG SjGOI GdOhd hfXGe GdMeGjI GdOhdjI dMbhb GdGfSGf hPdc ai VhA GMcGe cd ef GdbGfhf GdOhdi GdYGe GdeYGUQ HhLg YGe hGdbGfhf GdOhdi dMbhb GdGfSGf HhLg NGU hai VhA GdeHGOF GdJi GQSJgG eeGQSGJ GdefXeGJ hGdGLgRI GdOhdjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2007s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B437-459s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3eHOC GdSjGOI GdhWfjIs; (3fXGe GdMeGjI GdOhdjIs; (3fXGe GdMeGjI GdOhdjI dMbhb GdGfSGfs; (3GdGYdGf GdYGdei ddMbhb GdGfSGfs; (3ejKGb GdGee GdeJMOIs; (3GfJgGcGJ Mbhb GdGfSGfs; (3GdeMceI GdLfGFjI GdOhdjIs; (3GdLQGFe VO GdGfSGfjIs; (3GdJYGhf GdbVGFi GdOhdis; (3Mb GdJONd dJbOje GdeSGYOGJ GdGfSGfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs